Effect of Foot Reflexology on Anxiety of Mothers of High Risk Neonates undergone Cesarean Section: a Non Randomized Controlled Trial - Farideh Bastani; Elaheh Rouhi Rahim Begloo; Hamid Haghani (Tehran University of Medical Sciences, 2015)
Background & Aim: Anxiety is associated with postpartum mood disorder and is increased with birth of high risk neonates. Foot reflexology is a nursing intervention that can be used to reduce anxiety. T he aim of this study was to evaluate the effect of foot reflexology on anxiety in mothers with high risk neonates after Cesarean section s .   Methods & Materials: In this non-randomized clinical trial, 99 mothers having high risk neonates were recruited from the Womenchr('39')s General Hospital and Valieasr Hospital . The participants were allocated into three groups (n=33/group) using convenience sampling method . The group I received foot r eflexology for 40 minutes group II received leg massage and the control group received usual care after the Cesarean section. The Spielberger questionnaire was completed at baseline and three days after the interventions by the participants . Data were analyzed using the r epeated measure ANOVA and Chi-Squared in the SPSS-16 .    Results: At the baseline, there were no significant differences between the three groups in terms of demographic characteristics and the mean scores of anxiety . After the interventions, the mean score of anxiety was significantly lower in the reflexology and placebo groups than the control group (P<0.001). There was no significant difference between the reflexology and placebo groups in terms of the mean scores of anxiety (P>0.05). Comparing the mean score of anxiety between the reflexology (14.7±7.2) and placebo (9.4±8.5) groups indicated that the reflexology intervention was more effective in reducing anxiety .   Conclusion: The use of foot reflexology was effective in reducing anxiety. Nurses should use this non-pharmacologic method to control the symptoms of anxiety among mothers .